2020
DOI: 10.3389/fpsyg.2020.543773
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Silence: Enhanced Microstructural Changes in the Uncinate Fasciculus

Abstract: Silence is an important aspect of various meditation practices, but little work has focused specifically on the underlying neurophysiology of silence-related meditative practice, and on how it relates to the self-reported experiences of practitioners. To expand current knowledge regarding the neurophenomenology of silence in meditation, we directly investigated first-person reports of silence-related experiences during the practice of Quadrato Motor Training (QMT) and their association with changes in fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…So the article has formed the basis of a number of subsequent influential literature reviews, conceptual contributions, and methodological and empirical works; drawing from it, scholars have differentiated intuition from related constructs (Hodgkinson et al, 2008(Hodgkinson et al, , 2009aSadler-Smith, 2010, 2015Salas et al, 2010;Blume and Covin, 2011;Akinci and Sadler-Smith, 2012, 2013, 2020Baldacchino, 2013Baldacchino, , 2019Baldacchino et al, 2015;Healey et al, 2015;Pratt and Crosina, 2016;Calabretta et al, 2017;Okoli et al, 2021;Sadler-Smith et al, 2021). In addition, the article has spread over psychology and neuroscience (Hodgkinson et al, 2008;Hogarth, 2010;Gore and Sadler-Smith, 2011;Hodgkinson and Healey, 2011;Ben-Soussan et al, 2020;Keck and Tang, 2020;Korteling and Toet, 2020;Li et al, 2020;Stephens et al, 2020;West et al, 2020;Muñoz-Cobos and Postigo-Zegarra, 2021;Reynolds et al, 2021;Yu et al, 2021;Zhang et al, 2021), as well as distant disciplinary domains, such as medicine and health sciences (Glatzer et al, 2020;Cameron and Singh, 2021;Chlupsa et al, 2021) or engineering and design (Cash and Maier, 2021;de Rooij et al, 2021;Paige et al, 2021;…”
Section: No Agreementmentioning
confidence: 99%
“…So the article has formed the basis of a number of subsequent influential literature reviews, conceptual contributions, and methodological and empirical works; drawing from it, scholars have differentiated intuition from related constructs (Hodgkinson et al, 2008(Hodgkinson et al, , 2009aSadler-Smith, 2010, 2015Salas et al, 2010;Blume and Covin, 2011;Akinci and Sadler-Smith, 2012, 2013, 2020Baldacchino, 2013Baldacchino, , 2019Baldacchino et al, 2015;Healey et al, 2015;Pratt and Crosina, 2016;Calabretta et al, 2017;Okoli et al, 2021;Sadler-Smith et al, 2021). In addition, the article has spread over psychology and neuroscience (Hodgkinson et al, 2008;Hogarth, 2010;Gore and Sadler-Smith, 2011;Hodgkinson and Healey, 2011;Ben-Soussan et al, 2020;Keck and Tang, 2020;Korteling and Toet, 2020;Li et al, 2020;Stephens et al, 2020;West et al, 2020;Muñoz-Cobos and Postigo-Zegarra, 2021;Reynolds et al, 2021;Yu et al, 2021;Zhang et al, 2021), as well as distant disciplinary domains, such as medicine and health sciences (Glatzer et al, 2020;Cameron and Singh, 2021;Chlupsa et al, 2021) or engineering and design (Cash and Maier, 2021;de Rooij et al, 2021;Paige et al, 2021;…”
Section: No Agreementmentioning
confidence: 99%
“…In adults, there is evidence that the structural integrity of the uncinate fasciculus (Ben‐Soussan et al., 2020; Piervincenzi et al., 2017; Tang et al., 2012) or the degree of functional connectivity between the amygdala and prefrontal regions (Doll et al., 2016; Gotink et al., 2016) can be strengthened by training in a variety of mindfulness‐based techniques. Joss et al.…”
Section: Clinical Toolkitmentioning
confidence: 99%
“…For young children, ARC affect modulation exercises as described by Arvidson et al (2011) may be helpful, and in young adults, skills described by Hopper et al (2019). In adults, there is evidence that the structural integrity of the uncinate fasciculus (Ben-Soussan et al, 2020;Piervincenzi et al, 2017;Tang et al, 2012) or the degree of functional connectivity between the amygdala and prefrontal regions (Doll et al, 2016;Gotink et al, 2016) can be strengthened by training in a variety of mindfulness-based techniques. Joss et al (2020Joss et al ( , 2021 reported that mindfulness training also affected relative increases in hippocampal volume that were associated with performance on an episodic memory task as well as stress and depression levels.…”
Section: Tools For Overactive Threat Response Systemmentioning
confidence: 99%
“…In fact, neuroscientific studies have demonstrated that our brain can be regarded as fragmented, and that increased neuronal synchronization can enhance internal integrity [17]. This is especially the case within the alpha (8-12 Hz) band, which is related to cognitive flexibility, attention, and self-awareness [19,20].…”
Section: The Cognition-emotion-bodily Motion Trianglementioning
confidence: 99%